Endothelial Hypoxia-Inducible Factor-2α Is Required for the Maintenance of Airway Microvasculature. Issue 4 (22nd January 2019) - Jiang, Xinguo; Tian, Wen; Tu, Allen B.; Pasupneti, Shravani; Shuffle, Eric; Dahms, Petra; Zhang, Patrick; Cai, Haoliang; Dinh, Thanh T.; Liu, Bo; Cain, Corey; Giaccia, Amato J.; et al.
Abstract : Background: Hypoxia-inducible factors (HIFs), especially HIF-1α and HIF-2α, are key mediators of the adaptive response to hypoxic stress and play essential roles in maintaining lung homeostasis. Human and animal genetics studies confirm that abnormal HIF correlates with pulmonary vascular pathology and chronic lung diseases, but it remains unclear whether endothelial cell HIF production is essential for microvascular health. The large airway has an ideal circulatory bed for evaluating histological changes and physiology in genetically modified rodents. Methods: The tracheal microvasculature of mice, with conditionally deleted or overexpressed HIF-1α or HIF-2α, was evaluated for anatomy, perfusion, and permeability. Angiogenic signaling studies assessed vascular changes attributable to dysregulated HIF expression. An orthotopic tracheal transplantation model further evaluated the contribution of individual HIF isoforms in airway endothelial cells. Results: The genetic deletion of Hif-2α but not Hif-1α caused tracheal endothelial cell apoptosis, diminished pericyte coverage, reduced vascular perfusion, defective barrier function, overlying epithelial abnormalities, and subepithelial fibrotic remodeling. HIF-2α promoted microvascular integrity in airways through endothelial angiopoietin-1/TIE2 signaling and Notch activity. In functional tracheal transplants, HIF-2α deficiency in airway donors accelerated graft microvascular loss, whereas HIF-2α or angiopoietin-1 overexpression prolonged transplant microvascular perfusion. Augmented endothelial HIF-2α in transplant donors promoted airway microvascular integrity and diminished alloimmune inflammation. Conclusions: Our findings reveal that the constitutive expression of endothelial HIF-2α is required for airway microvascular health. Abstract : Supplemental Digital Content is available in the text.